2020
DOI: 10.3390/ijerph17144919
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Suitability of an Existing Job–Exposure Matrix for the Assessment of Exposure of UK Biobank Participants to Dust, Fumes, and Diesel Exhaust Particulates

Abstract: Many epidemiological studies have shown an association between outdoor particulate air pollutants and increased morbidity and mortality. Inhalation of ambient aerosols can exacerbate or promote the development of cardiovascular and pulmonary diseases as well as other diseases, such as type 2 diabetes mellitus (T2DM) and neurodegenerative diseases. Occupational exposure to dust, fumes and diesel exhaust particulates can also cause adverse health outcomes and there are numerous occupations where workers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…To the best of our knowledge, although there are many studies that examine the relationship between occupational exposures such as night-shift work, job strain, or specific substances such as solvents and diabetes [ 48 , 49 , 50 ] or dementia [ 51 , 52 , 53 , 54 , 55 ], this is the first study to investigate an association between occupational exposure to PM that are similar to environmental air pollution exposure and both health outcomes. We relied on the ACE JEM to assign exposure probability and intensity to jobs, although from our earlier work it is likely that these assignments were most reliable for highly exposed jobs and for jobs assigned as unexposed [ 23 ]. We chose to recategorise into exposed and unexposed to attempt to minimise the potential for misclassification in the analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To the best of our knowledge, although there are many studies that examine the relationship between occupational exposures such as night-shift work, job strain, or specific substances such as solvents and diabetes [ 48 , 49 , 50 ] or dementia [ 51 , 52 , 53 , 54 , 55 ], this is the first study to investigate an association between occupational exposure to PM that are similar to environmental air pollution exposure and both health outcomes. We relied on the ACE JEM to assign exposure probability and intensity to jobs, although from our earlier work it is likely that these assignments were most reliable for highly exposed jobs and for jobs assigned as unexposed [ 23 ]. We chose to recategorise into exposed and unexposed to attempt to minimise the potential for misclassification in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…JEMs are also generally not good at identifying small effects, especially JEMs like the ACE JEM that are generated from subjective information rather than objective measurements [ 59 ]. From our earlier evaluation of the ACE JEM it was observed that the assignments for medium and low exposed jobs were less reliable than for high and unexposed jobs [ 23 ]. Moreover, there may be problems in the JEM’s coding for men and women, as it seems there is inconsistency between the assessments for the two gender.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations